Promoting literature to build college students’ socio-political awareness in the EFL reading class - Dian Nurrachman (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2011)
The relationship of classroom to the outside world is a reciprocal one, meaning that classrooms are part of the world in which socio-politics is included. The students become successful literary readers as well as critical thinkers who have socio-political awareness if the classroom conducts an ‘extensive reading’ by ‘letting the students in’. The implication of these understandings for the work of EFL teachers is to give a vindication that literature can fully become the best authentic material in the teaching and learning of English, especially for reading class of the college students. In certain ways, this is also aimed to promote literature as a device to build students’ socio-political awareness, because literature, we are told, is vitally engaged with the living situations of men and women: it’s concrete rather than abstract, displays life in all its rich variousness.